2009
DOI: 10.1002/cncr.24484
|View full text |Cite
|
Sign up to set email alerts
|

Why are pretreatment prostate‐specific antigen levels and biochemical recurrence poor predictors of prostate cancer survival?

Abstract: An ultra scale‐down (USD) device that provides insight of how industrial homogenization impacts bioprocess performance is desirable in the biopharmaceutical industry, especially at the early stage of process development where only a small quantity of material is available. In this work, we assess the effectiveness of focused acoustics as the basis of an USD cell disruption method to mimic and study high‐pressure, step‐wise homogenization of rec Escherichia coli cells for the recovery of an intracellular protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 73 publications
2
16
0
Order By: Relevance
“…Its value in predicting survival is less clear, however. Like many other investigators, we have also found the iPSA level to be a good predictor of biochemical failure-free survival (BFFS) in the TROG 96.01 dataset (3,7). However, in this same dataset, the iPSA level did not predict PC-specific survival (PCSS).…”
Section: Introductionsupporting
confidence: 51%
See 1 more Smart Citation
“…Its value in predicting survival is less clear, however. Like many other investigators, we have also found the iPSA level to be a good predictor of biochemical failure-free survival (BFFS) in the TROG 96.01 dataset (3,7). However, in this same dataset, the iPSA level did not predict PC-specific survival (PCSS).…”
Section: Introductionsupporting
confidence: 51%
“…In the same dataset, we found that the occurrence of biochemical failure itself, however, is a far weaker predictor of cancer death than time to biochemical failure (3).…”
Section: Introductionmentioning
confidence: 84%
“…The two reasons for hormone manipulation were (1) to downsize the prostate, as in most cases the gland was considered too large for needle placement. If gland size had not reduced to a transverse width of less than 5 cm by that time, they were switched to EBRT alone; (2) in the context of a novel technique, the use of hormones in the lower risk groups was deemed to be a safer approach. Brachytherapy was delivered before EBRT in most cases.…”
Section: Treatmentmentioning
confidence: 99%
“…The current Phoenix consensus definition of biochemical failure after external beam radiation therapy (EBRT) or brachytherapy with or without hormonal therapy (HT) is a rise by 2 ng/ mL or more above the nadir PSA (nPSA) (1). However, biochemical failure itself has a poor specificity for predicting subsequent cancer death (2); and given the slow natural history of PC, many post-treatment years may have passed before biochemically relapsed disease becomes clinically apparent. Hence, study into various other PSA response patterns have aimed to provide earlier and more accurate surrogate endpoints of long-term outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…In the same dataset, Denham and colleagues also determined how the occurrence of biochemical failure itself related to prostate cancer-specific mortality and demonstrated that the occurrence of biochemical failure was a far weaker predictor of cancer death than time to biochemical failure (Denham et al 2009). It was also shown that prognostic factors for early cancer death changed dramatically at biochemical recurrence.…”
mentioning
confidence: 91%